2015
DOI: 10.1523/jneurosci.0540-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging of Rats with Experimental Autoimmune Encephalomyelitis Reveals Brain Cortex Remodeling

Abstract: Cortical reorganization occurring in multiple sclerosis (MS) patients is thought to play a key role in limiting the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…Recently, in a fMRI study, Tambalo et al investigated the functional response to somatosensory stimulation of the forepaw in DA Dark Agouti rats with experimental autoimmune encephalomyelitis (EAE), a widely accepted preclinical model of chronic multiple sclerosis (MS). 32 Alterations of the functional response of EAE mice (in the relapsing and chronic phases) were found and this finding was in line with human fMRI studies showing that cortical reorganization occurs in MS patients. 33 These results provide additional support to the validity of the DA EAE rat model for fMRI studies and for the development of innovative therapies in EAE/MS research.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Recently, in a fMRI study, Tambalo et al investigated the functional response to somatosensory stimulation of the forepaw in DA Dark Agouti rats with experimental autoimmune encephalomyelitis (EAE), a widely accepted preclinical model of chronic multiple sclerosis (MS). 32 Alterations of the functional response of EAE mice (in the relapsing and chronic phases) were found and this finding was in line with human fMRI studies showing that cortical reorganization occurs in MS patients. 33 These results provide additional support to the validity of the DA EAE rat model for fMRI studies and for the development of innovative therapies in EAE/MS research.…”
Section: Introductionsupporting
confidence: 82%
“…33 These results provide additional support to the validity of the DA EAE rat model for fMRI studies and for the development of innovative therapies in EAE/MS research. 32 In animals, fMRI can also be performed using exogenous paramagnetic or superparamagnetic contrast agents. When confined in the vascular space, they create a strong inhomogeneity in the static magnetic field and consequently a decrease in signal intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [35] measured microvascular volume distribution in mice using a 30 mgFe/kg injection at 9.4 T and demonstrated that CBV in the cerebral cortex is higher in transgenic APP mice, an experimental model of Alzheimer's disease, than in controls. CBV-weighted functional MRI (fMRI) has been extensively used in experimental fMRI [36,37]; thanks to the increased sensitivity of CBV-weighted contrast compared with classical blood oxygen level-dependent (BOLD) contrast. At 7 T, 15-20 mg Fe/kg ultrasmall superparamagnetic iron oxides improve functional contrast-to-noise ratio (CNR) by 70% in rats compared with BOLD contrast [38].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-processing of data included: (i) export into DICOM format from ParaVision 6.0.1 (Bidgood Jr et al, 1997); (ii) conversion into NifTI using the dcm2niix converter (64-bit Linux version 5 May 2016) (Rorden et al, 2007); (iii) reorienting the brain into leftanterior-superior (LAS) axes (radiological view); and (iv) skull-stripping using the qimask utility from QUIT (QUantitative Imaging Tools) (Wood, 2018). The voxel sizes were then upscaled by a factor of 10 (Tambalo et al, 2015).…”
Section: Rs-fmri Datamentioning
confidence: 99%